Effect of sulfurization time on the performance of monoclinic Cu2SnS3 solar cells. (August 2019) - Pallavolu, Mohan Reddy; Kim, Chang-Duk; Minnam Reddy, Vasudeva Reddy; Gedi, Sreedevi; Park, Chinho
Highlights: Cu2 SnS3 films were deposited by rapid thermal sulfurization process. Effect of sulfurization time on the properties of M-Cu2 SnS3 films was studied. Single phase M-Cu2 SnS3 thin films with high crystallinity were obtained for 10 min. Abstract: In this study, monoclinic (M)-Cu2 SnS3 (CTS) thin films were prepared by high vacuum (10 Pa) rapid thermal sulfurization of sputtered Cu/Sn/Cu metallic layers. The effect of sulfurization time (1 min, 5 min, 10 min, and 20 min) on the crystal structure, morphology, optical studies, and electrical studies of the M-CTS thin films was investigated. The structural studies assessed the formation of M-CTS single phase for the films sulfurized ≥10 min and the secondary phases in addition to M-CTS at shorter sulfurization durations of ≤5 min. The single phase M-CTS films sulfurized at 10 min showed dense morphology and had a band gap energy of 0.92 eV. The present results indicated that the short sulfurization time of 10 min is sufficient for the formation of single phase M-CTS thin films. The fabricated M-CTS solar cell showed a PCE of 0.51% for the films sulfurized at 10 min.